The Complexities of Cooperation Over Outer Space: Political Practice and Prospects - Stanislav V. Solovyev (RUDN Journal of Political Science, 2023)
The formation of the political and legislative regime concerning use of outer space becomes every day more relevant. The research is intended to further expand current studies devoted to this issue by providing thorough information on the formation of the world’s first international legal framework for outer space territories use. The author examines in chronological order the regulatory and institutionalization process of the world’s first informal system that determined interaction among the participants of the space race. At the same time, this study provides a detailed analysis of the problems related to the formation of a comprehensive international regime, allowing author to make a conclusion about the ineffectiveness of the current system based on targeted international treaties and the necessity of modifying the formalisation approaches. In addition, article proposes potential scenarios for the formation of a political and legal outer space regime. The author assesses the possibility of establishing military hegemony alongside militarisation of outer space, analyses prospects for a codified peaceful co-development regime in the absence of workable space diplomacy initiatives, as well as considers the possibility of privatisation of space under free competition and the probability of preserving the current regime.